Factors Affecting Success in Administration of Schools under the Supervision of Chiang Rai Primary Educational Service Area Office 3 - Khandet, Nittaya; Malaitao, Thararat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to study 1) success level factors affecting school administration; 2) success level in school administration; and 3) success factors affecting school administration. Five-rating scale questionnaire was used as a research tool. Data were analyzed using frequency, percentage, mean, standard deviation and stepwise multiple regression analysis. The results showed that 1) success factors in school administration as a whole were at a high level. Considering each factor, it was found that the factor with the highest mean was school administrators followed by teachers and educational personnel, and the lowest mean factor was students 2). Overall success in school administration was at a high level. Considering each aspect, it was found that the aspect with the highest average was student development followed by teacher development, and educational personnel, and the aspect with the least average value was community participation. 3) Success factors in school administration were found that school administrator factor, engagement factor, teachers and educational personnel factor, and school factor were at statistically significance at the level of 0.05 that affected success in school administration. The prediction efficiency was 74.30%.